TANTANGAN IMPLEMENTASI AKOMODASI BAGI PESERTA DIDIK PENYANDANG DISABILITAS DI TAMAN KANAK-KANAK - Gita, Putu; Juita, Kristina Helena; Kurniastuti, Irine (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of inclusive education at the Kindergarten level represents a strategic effort to ensure the learning rights of students with disabilities through the provision of Reasonable Accommodation (RA), as stipulated in Regulation of the Minister of Education, Culture, Research, and Technology No. 48 of 2023. In line with this, the present study aims to examine the challenges faced by teachers in accommodating the learning needs of students with disabilities in the kindergarten environment. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with the school principal and classroom teachers, as well as direct observations of the teaching and support processes provided to students with disabilities. The findings indicate that teachers encounter several challenges, including limited infrastructure and educational play resources, low levels of specific teacher competence in addressing diverse disability characteristics, and ineffective collaboration with parents. These conditions affect the effectiveness of inclusive learning implementation and the ability of teachers to design strategies that are responsive to the individual needs of students. Therefore, this study recommends strengthening teacher capacity through continuous professional development and concrete policy interventions to support teacher adaptation in inclusive kindergarten settings.